Comparative Performance Evaluation of Scheduling Algorithms using 5G‑Air‑Simulator - Moaath Saleh Abdulrahman; Buthaina Mosa Omran (Journal of Engineering)
The Third Generation Partnership specified the 5th Generation New Radio standard to fulfill the growing demand of wireless traffic and the increased need for higher data rates. With the spread of new applications, efficient scheduling algorithms are mandatory to handle the allocation of the limited spectrum resources to various types of traffic and to guarantee the requirements of the quality of service and the quality of experience informed by users. In this paper several scheduling algorithms specifically Round Robin, Best Channel Quality Indicator, Proportional Fair, Modified Largest Weighted Delay First, Exponential Proportional Fair, and Logarithm Rule are evaluated and their performances are compared to each other. The simulation shows that Round Robin and Proportional Fair perform well for non-real time services and Voice over Internet Protocol traffic, particularly for simple systems since they offer high level of fairness between users and low packet loss ratio. On the other hand, Best Channel Quality Indicator produces poor performance for its very low fairness index, very high packet loss ratio and long delay values making it impractical to implement in most scenarios. The other three algorithms perform effectively for real time services specifically for video traffic. While Exponential Proportional Fair algorithm has the lowest values of delay, Logarithm Rule algorithm gives the highest data rate and the lowest packet loss ratio with high index of fairness.